2023
DOI: 10.2186/jpr.jpr_d_21_00308
|View full text |Cite
|
Sign up to set email alerts
|

Effect of multi-purpose primer on bonding of acrylic resin to cast titanium and gold alloy after airborne-particle abrasion

Abstract: Surface treatment with primers containing functional monomers is a simple way to obtain high bond strength. Acidic functional monomers such as 10-methacryloyloxydecyl dihydrogen phosphate (MDP), which act on the oxide film produced on the surface of nonnoble metals, were initially used [5]. The effectiveness of MDP on titanium has been previously demonstrated [6][7][8]. Tsuchimoto et al.[9] refered to the condition of titanium surface being important for bonding using MDP. MDP and other acidic functional mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…Specifically, EOP-and ALP-priming agents containing 10-methacryloyloxydecyl dihydrogen phosphate (MDP) monomers demonstrated good bonding durability (category A-a). This result agrees with previous studies, although the types of luting materials, titanium alloys, primers, and experimental conditions were not identical [11][12][13][14][15][16][17][19][20][21][22][23] . Tsuchimoto et al reported the effectiveness of MDP monomer on the adhesion of pure titanium.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Specifically, EOP-and ALP-priming agents containing 10-methacryloyloxydecyl dihydrogen phosphate (MDP) monomers demonstrated good bonding durability (category A-a). This result agrees with previous studies, although the types of luting materials, titanium alloys, primers, and experimental conditions were not identical [11][12][13][14][15][16][17][19][20][21][22][23] . Tsuchimoto et al reported the effectiveness of MDP monomer on the adhesion of pure titanium.…”
Section: Discussionsupporting
confidence: 91%
“…The Ti-15Mo-5Zr-3Al alloy consisted of Ti, Mo, Zr, and Al, and no noble metal elements were incorporated. Four acidic primers for treating the Ti-15Mo-5Zr-3Al alloy and its component metals were selected because thione and sulfide monomers are known to be effective for priming noble metal alloys 15,23,34) but ineffective for priming base metals, including titanium 15,23) . The first null hypothesis was that the bond strength and durability of acrylic resin bonded to a titanium alloy would not be influenced by the type of priming agent.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations